2010
DOI: 10.1111/j.1469-8749.2009.03473.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of individuals with cerebral palsy receiving continuous intrathecal baclofen treatment: a matched‐cohort study

Abstract: AIM To determine whether intrathecal baclofen (ITB) changes mortality risk in persons with cerebral palsy (CP).METHOD Records were reviewed for all persons with CP who were managed with ITB for hypertonicity at a specialty hospital in Minnesota between May 1993 and August 2007. A comparison cohort was randomly selected from clients of the California Department of Developmental Services who were initially evaluated between 1987 and 1990 and were matched to those with ITB for age, sex, Gross Motor Function Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Some work has been done in this area, including studies of selective dorsal rhizotomy 14,15 and intrathecal baclofen. 16 Much more research needs to focus on this area, including studies of intensive therapy interventions and other treatments into which families heavily invest their time and resources with the hope of maximizing their child's potential as an adult. Thirdly, there were many questions about physiology of the ageing process combined with a developmental neurological disorder such as CP.…”
Section: Discussionmentioning
confidence: 99%
“…Some work has been done in this area, including studies of selective dorsal rhizotomy 14,15 and intrathecal baclofen. 16 Much more research needs to focus on this area, including studies of intensive therapy interventions and other treatments into which families heavily invest their time and resources with the hope of maximizing their child's potential as an adult. Thirdly, there were many questions about physiology of the ageing process combined with a developmental neurological disorder such as CP.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral Palsy Results from a number of studies suggest that IT baclofen therapy is useful in reducing spasticity, decreasing pain frequency and severity, and improving gross motor function in patients with cerebral palsy (207–211). One review of records from IT baclofen‐treated patients with cerebral palsy and patients with cerebral palsy who did not receive IT baclofen suggested that IT baclofen therapy does not increase mortality and may improve life expectancy (212). This suggestion is based on a small retrospective single center study and more research is needed.…”
mentioning
confidence: 99%
“…Recent longitudinal studies support both ef fi cacy and safety in the continuous use of ITB for children with spasticity as well as other movement disorders caused from various underlying conditions, including cerebral palsy, stroke, multiple sclerosis, myelomeningocele, and head or spinal injury (Bergenheim et al 2003 ;Krach et al 2010 ;Morton et al 2011 ;Ramstad et al 2010 ;Ward et al 2009 ) . Recent longitudinal studies support both ef fi cacy and safety in the continuous use of ITB for children with spasticity as well as other movement disorders caused from various underlying conditions, including cerebral palsy, stroke, multiple sclerosis, myelomeningocele, and head or spinal injury (Bergenheim et al 2003 ;Krach et al 2010 ;Morton et al 2011 ;Ramstad et al 2010 ;Ward et al 2009 ) .…”
Section: Intrathecal Baclofenmentioning
confidence: 97%